2016
DOI: 10.1007/s11604-016-0590-y
|View full text |Cite
|
Sign up to set email alerts
|

Is it essential to use fiducial markers during cone-beam CT-based radiotherapy for prostate cancer patients?

Abstract: Our study demonstrated that CBCT-FM was not superior to CBCT-P for image-guided radiotherapy in prostate cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…One or more GTVs could be contoured per patient. Based on our previous findings, we did not routinely use gold fiducial markers 14 …”
Section: Methodsmentioning
confidence: 99%
“…One or more GTVs could be contoured per patient. Based on our previous findings, we did not routinely use gold fiducial markers 14 …”
Section: Methodsmentioning
confidence: 99%
“…I agree with Dr. Parker that FMs are not superior to noninvasive techniques such as CBCT in the initial setup alignment of prostate patients . Dr. Parker went further to present an argument for an alternative role for FMs whereby they are used to monitor prostate intrafraction motion.…”
Section: Against the Proposition: Brent C Parker Phdmentioning
confidence: 84%
“…This may lead one to conclude that fiducials are no longer needed in prostate radiotherapy. Indeed, studies have shown that the use of implanted fiducials imaged with orthogonal planar imaging is not superior to CBCT for patient positioning . Thus, there is intrinsically no “need” for fiducials in the traditional use of initial patient positioning.…”
Section: Against the Proposition: Brent C Parker Phdmentioning
confidence: 99%
“…In addition, VMAT (especially with FFF beam) has a shorter treatment time than CyberKnife [ 19 ]. VMAT can be performed without fiducial markers using cone-beam CT and other matching techniques [ 24 ]. These are significant advantages for patients who desire minimally invasive treatment and are sufficient reasons to perform SBRT with VMAT, regardless of whether the institution owns a CyberKnife.…”
Section: Discussionmentioning
confidence: 99%